Planting the Anthropocene : Rhetorics of Natureculture - Clary-Lemon, Jennifer (Book collections on Project MUSE., 2019)
"A rhetorical look into the world of silviculture--industrial tree planting--and engages themes of nature, culture, and environmental change. Bringing together the work of material ecocriticism and critical affect studies in service of a new materialist environmental rhetoric and works through complex scenes of anthropogenic labor"--Provided by publisher